The peacekeeping economy using economic relationships to build a more peaceful, prosperous, and secure world - Dumas, Lloyd J. (Yale University Press, 2011)
The idea that military strength is virtually synonymous with security is deeply entrenched and widely held. This title considers the practical problems of the transition from military-based security arrangements to "economic peacekeeping", and the effects of demilitarized security on economic development and prosperity